2020
DOI: 10.1016/j.gaitpost.2020.06.030
|View full text |Cite
|
Sign up to set email alerts
|

A spatio-temporal and kinematic description of self-selected walking in adults with Achondroplasia

Abstract: Background: Achondroplasia is characterised by a shorter appendicular limb to torso ratio, compared to age matched individuals of average stature (controls). Despite the well documented shorter leg length of individuals with compared to controls, there are few complete descriptions of gait kinematics reported for the population. Aim: The aim of this study was to report the spatio-temporal and kinematic characteristics of self-selected walking (SSW) in a group with Achondroplasia (N = 10) and age matched group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
(50 reference statements)
1
14
0
Order By: Relevance
“…Similarly, individual T17 has likely exercised great loading at push-off, similar to barefoot hunter-gatherers or those wearing minimalistic soft-coverings, though such an explanation is highly improbable as the sole explanation for our finding given the low mobility of hypochondroplasic individuals (Haga, 2004;Sims et al, 2019Sims et al, , 2020. Indeed, recent kinematic studies on the gait cycle have shown that individuals with achondroplasia walk at a slower speed have shorter stride lengths and higher frequencies of strides compared with a group of healthy individuals, largely because of the shorter, disproportionate leg length of the former (Sims et al, 2019(Sims et al, , 2020. High stride frequencies in T17 may be a contributing factor to the more robust (i.e., short and broad) talar neck likely due to higher load given more impacts per given distance, though kinematic studies on hypochondroplasic individuals would be necessary to test this hypothesis.…”
Section: External Talar Shapementioning
confidence: 87%
See 4 more Smart Citations
“…Similarly, individual T17 has likely exercised great loading at push-off, similar to barefoot hunter-gatherers or those wearing minimalistic soft-coverings, though such an explanation is highly improbable as the sole explanation for our finding given the low mobility of hypochondroplasic individuals (Haga, 2004;Sims et al, 2019Sims et al, , 2020. Indeed, recent kinematic studies on the gait cycle have shown that individuals with achondroplasia walk at a slower speed have shorter stride lengths and higher frequencies of strides compared with a group of healthy individuals, largely because of the shorter, disproportionate leg length of the former (Sims et al, 2019(Sims et al, , 2020. High stride frequencies in T17 may be a contributing factor to the more robust (i.e., short and broad) talar neck likely due to higher load given more impacts per given distance, though kinematic studies on hypochondroplasic individuals would be necessary to test this hypothesis.…”
Section: External Talar Shapementioning
confidence: 87%
“…High levels of ankle dorsiflexion and the presence of an anterolateral talar facet may be associated with the hypochondroplasic condition of T17. Greater ankle dorsiflexion may compensate for an increased foot/leg length ratio by preventing toe contact with the ground during swing phase of the gait cycle (Sims et al, 2019(Sims et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations